CILP1 as a biomarker for right ventricular dysfunction in patients with ischemic cardiomyopathy. (25th March 2022) - Keranov, Stanislav; Jafari, Leili; Haen, Saskia; Vietheer, Julia; Kriechbaum, Steffen; Dörr, Oliver; Liebetrau, Christoph; Troidl, Christian; Rutsatz, Wiebke; Rieth, Andreas; Hamm, Christian W.; Nef, Holger; et al.
Abstract: The aim of this study was to evaluate the cartilage intermediate layer protein 1 (CILP1) as a biomarker of right ventricular dysfunction in patients with ischemic cardiomyopathy (ICM). CILP1 plasma concentrations were measured in 98 patients with ICM and 30 controls without any cardiac abnormalities. All participants underwent cardiac magnetic resonance imaging. Median CILP1 concentrations were higher in ICM than in controls. In the tertile analysis, low right ventricular ejection fraction (RVEF) and high right ventricular end‐systolic volume index and N‐terminal pro‐brain natriuretic peptide (NT‐proBNP) were associated with higher CILP1 levels in ICM. However, there were no associations between CILP1 concentrations and left ventricular (LV) parameters in this group. In receiver‐operating characteristic (ROC) analysis CILP1 was a good predictor of RVEF < 40% with an optimal cut‐off value of 3545 pg/ml in ICM, whereas it was not predictive of LV ejection fraction (LVEF) < 40% (area under the curve [AUC] = 0.57) There was no significant difference between the ROC curves of CILP1 (AUC = 0.72) and NT‐proBNP (AUC = 0.77) for RVEF < 40% ( p = 0.42). In multivariable regression analysis, RVEF was the only independent predictor of elevated CILP1. CILP1 and LVEF were the only independent predictors of RVEF < 40% in ICM. Our analysis demonstrates the potential role of CILP1 as a novel cardiac biomarker of prognostically relevant RV dysfunction in patients with ICM.